Ecological validity as a key feature of external validity in research on human development - Diehl, Manfred; Wahl, Hans-Werner; Freund, Alexandra M. (Research in human development, 2017)
This issue addresses the topic of ecological validity in research in human development across the life span. Although recent developments in study design, data collection methods, and data analysis techniques have greatly advanced researchers’ ability to collect large amounts of data on large groups of individuals in natural settings, it is important to approach these data with a reflected understanding of their ecological validity. Just because data were collected using everyday and familiar stimuli or ecological momentary assessment methods does not mean automatically that the ecological validity of these data is guaranteed and can go unquestioned.